2002
DOI: 10.1109/10.972841
|View full text |Cite
|
Sign up to set email alerts
|

A time-harmonic inverse methodology for the design of RF coils in MRI

Abstract: An inverse methodology is described to assist in the design of radio-frequency (RF) coils for magnetic resonance imaging (MRI) applications. The time-harmonic electromagnetic Green's functions are used to calculate current on the coil and shield cylinders that will generate a specified internal magnetic field. Stream function techniques and the method of moments are then used to implement this theoretical current density into an RF coil. A novel asymmetric coil operating for a 4.5 T MRI machine was designed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…We have previously shown that coils modeled in this produce experimental results in prototypes that conform closely to predictions [3].…”
Section: S)mentioning
confidence: 50%
See 3 more Smart Citations
“…We have previously shown that coils modeled in this produce experimental results in prototypes that conform closely to predictions [3].…”
Section: S)mentioning
confidence: 50%
“…where w is the diameter of the wire and C is the perimeter of the loop; G(r|r ) is the free-space Green's function; and J (r ) is the current flowing in the loop given by (3). Assuming the quasi-static case where current is uniformly distributed along the wire, we assign I j = 1 and G(r|r ) = 1/|r − r |.…”
Section: Theory and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dependent of the specific characteristics of the problem, a number of dedicated approaches have been developed. Recent examples include the design of antennas [8], gradient coils for MRI [11] and magnets for MRI [7]. These examples apply the stream function indirectly to get the conductor shape, after determining the (surface) current density, from which the stream function is constructed.…”
Section: Introductionmentioning
confidence: 99%